IT transfer program in the creation of innovative and loyal IT professionals in Malaysia - Ibrahim, Huda; Yussof, Mohammed; Kasimin, Hasmiah; Shaik Osman, Wan Rozaini; Mat Aji, Zahurin; Othman, Nafishah; Abdul Razak, Rafidah; Wahid, Juliana (2006)
Mobility and turnover among IT professionals is a lost to Malaysian organizations since it disrupts project schedules and increases retraining cost and time. One major reason for leaving the current job is a small opportunity for self and career advancement in the former organization. To meet this professionals’ demand, this paper suggests organizations in Malaysia to develop and implement a learning mechanism through the creation of Information Technology Transfer (ITT) Program. The case studies in Malaysia have identified that a good ITT program can play an important role towards creating and maintaining pool of knowledge and professional workers. It is also helpful in supporting organizations to establish longer-term IT transfer and new learning strategies and provide personalized coaching to IT professionals no matter where they are at the moment of need. The program can be fully benefited if it is built with specific and well-planned objectives, design and delivery, monitoring and evaluation mechanism, and benefits.